2006
DOI: 10.1128/jb.00884-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ExsC and ExsD Self-Association and Heterocomplex Formation

Abstract: Expression of the Pseudomonas aeruginosa type III secretion system (T3SS) is induced by calcium depletion and is positively regulated by the ExsA transcriptional activator and negatively regulated by the ExsD antiactivator. Under conditions permissive for expression of the T3SS, the negative regulatory activity of ExsD is antagonized by a direct binding interaction with ExsC. In the present study, the ExsC-ExsD binding interaction was characterized. Individually, both ExsC and ExsD form self-associated complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
5
33
0
Order By: Relevance
“…For this reason ExsD was coexpressed with either ExsC His or ExsA His from the dual expression vector pCOLADuet-1 in E. coli and purified by Ni 2ϩ affinity chromatography. Both the purified ExsD·ExsC His and ExsD·ExsA His complexes were soluble based on resistance to high-speed sedimentation (100,000 ϫ g for 30 min), and both eluted from gel filtration columns as single included peaks with apparent molecular masses of 186 and 97 kDa, respectively (data not shown), which is consistent with previous studies (20,28).…”
Section: Reconstitution Of the Exsadce Regulatory Cascade In Vitrosupporting
confidence: 90%
“…For this reason ExsD was coexpressed with either ExsC His or ExsA His from the dual expression vector pCOLADuet-1 in E. coli and purified by Ni 2ϩ affinity chromatography. Both the purified ExsD·ExsC His and ExsD·ExsA His complexes were soluble based on resistance to high-speed sedimentation (100,000 ϫ g for 30 min), and both eluted from gel filtration columns as single included peaks with apparent molecular masses of 186 and 97 kDa, respectively (data not shown), which is consistent with previous studies (20,28).…”
Section: Reconstitution Of the Exsadce Regulatory Cascade In Vitrosupporting
confidence: 90%
“…By substitution of charged residues with alanine or glycine, Lykken et al 49 identified several ExsC mutants that were not able to complement the phenotype of exsC mutant. Nevertheless, these mutants were still able to bind ExsD, suggesting that binding of ExsC with ExsD is not sufficient for the induction of T3SS in Pseudomonas.…”
Section: Discussionmentioning
confidence: 99%
“…ExsD functions as an antiactivator by directly binding to the amino-terminal domain (NTD) of ExsA and inhibiting ExsA-dependent transcription (9,10). ExsC is an anti-antiactivator that binds to and antagonizes the inhibitory activity of ExsD (11)(12)(13). The final component of the cascade, ExsE, is a secreted substrate of the type III export machinery.…”
mentioning
confidence: 99%